Skeptical environmentalism : the limits of philosophy and science - Kirkman, Robert, 1968- (Indiana University Press, 2002)
In Skeptical environmentalism, Robert Kirkman raises doubts about the speculative tendencies elaborated in environmental ethics, deep ecology, social ecology, postmodern ecology, ecofeminism, and environmental pragmatism. Drawing on skeptical principles introduced by David Hume, Kirkman takes issue with key tenets of speculative environmentalism, namely that the natural world is fundamentally relational, that humans have a moral obligation to protect the order of nature, and that understanding the relationship between nature and humankind holds the key to solving the environmental crisis. Engaging the work of Kant, Hegel, Descartes, Rousseau, and Heidegger, among others, Kirkman reveals the relational worldview as an unreliable basis for knowledge and truth claims, and as harmful to the intellectual sources from which it takes inspiration. Exploring such themes as the way knowledge about nature is formulated, what characterizes an ecological worldview, how environmental worldviews become established, and how we find our place in nature, Skeptical environmentalism advocates a shift away from the philosopher's privileged position as truth seeker toward a more practical thinking that balances conflicts between values and worldviews.